Multifunctional light-activatable nanocomplex conducting temperate-heat photothermal therapy to avert excessive inflammation and trigger augmented immunotherapy. (November 2022) - Li, Lu; Liang, Xiuqi; He, Tao; Li, Xinchao; Huang, Xianzhou; Wang, Ning; Shen, Meiling; Shu, Yaqian; Wu, Rui; Zhang, Miaomiao; Wu, Qinjie; Gong, Changyang
Abstract: Photothermal therapy (PTT) has been known as an effective weapon against cancer. However, the necrosis induced by hyperthermia post PTT can trigger excessive inflammation response and arouse tumor self-protection resulting in tumor immunosuppression, metastasis and recurrence. To settle this issue, we here reported a m ulti functional l ight-a ctivatable n anocomplex (MILAN) to avoid hyperthermia and achieve temperate-heat PTT for extensive apoptosis, but not necrosis, and further antitumor immune response augmentation to inhibit metastasis and recurrence. Upon NIR irradiation, MILAN would controllably maintain around 43 °C, thus evoking the temperature-triggered phase transformation for the controllable drug release. Then, the released gambogic acid broke the thermoresistance of tumor cells, realizing enhanced apoptosis. Thereafter, the generated tumor-associated antigen accompanied with MILAN could facilitate dendritic cells (DCs) maturation for improved antigen presentation. Furthermore, MILAN promoted the tumor perfusion of DCs and T lymphocytes in triple-negative breast cancer (TNBC) models. Simultaneously, the immunosuppressive microenvironment was relieved and a strong systemic immune response was elicited against tumor progress through MILAN. Consequently, systemic immunity and persistent immune memory effect were fortified for pronounced cancer metastasis and recurrence inhibition. This work tactfully avoids the side effects of hyperthermia and brought a novel insight into cancer immunotherapy against TNBC.